Agricultural market reforms and technology adoption in Senegal - Bernard, Tanguy; Mbaye, Samba; de Janvry, Alain; Sadoulet, Elisabeth (Abdul Latif Jameel Poverty Action Lab, 2017)
Many smallholder farmers in sub-Saharan Africa do not use basic agricultural technologies to improve crop quality. In the Senegal River Valley, researchers tested whether receiving advance information on a market reform—introducing quality labels for onions and selling by weight—would lead to changes in farmers’ production habits.